2015
DOI: 10.1002/for.2384
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Based on Decomposed Financial Return Series: A Wavelet Analysis

Abstract: We transform financial return series into its frequency and time domain via wavelet decomposition to separate shortrun noise from long-run trends and assess the relevance of each frequency to value-at-risk (VaR) forecast. Furthermore, we analyze financial assets in calm and turmoil market times and show that daily 95% VaR forecasts are mainly driven by the volatility that is captured by the first scales comprising the short-run information, whereas more timescales are needed to adequately forecast 99% VaR. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…These findings can be important for investors when building their expectations about future oil prices over several horizons based on the current level of uncertainty. This is also in line with findings of previous studies that already showed the relevance of wavelet decomposition for forecasting returns on financial markets (Berger, 2016;Faria and Verona, 2018;Risse, 2019). *** Insert Figure 8 about here ***…”
Section: Disaggregated Perspectivesupporting
confidence: 90%
See 1 more Smart Citation
“…These findings can be important for investors when building their expectations about future oil prices over several horizons based on the current level of uncertainty. This is also in line with findings of previous studies that already showed the relevance of wavelet decomposition for forecasting returns on financial markets (Berger, 2016;Faria and Verona, 2018;Risse, 2019). *** Insert Figure 8 about here ***…”
Section: Disaggregated Perspectivesupporting
confidence: 90%
“…on momentum trading with respect to different frequencies which enables us to examine investors' sentiment at various horizons. This decomposition mimics the heterogeneity of agents with regard to different consumption requirements, risk tolerance levels, assimilation of information, institutional constraints and heterogeneous beliefs (Chakrabarty et al, 2015) and is also able to improve return forecasts in financial markets (Berger, 2016;Faria and Verona, 2018;Risse, 2019). For instance, negative news may be seen as a selling signal for short-term investors, while long-term investors may interpret the same news as buying opportunity.…”
Section: Introductionmentioning
confidence: 97%
“…4 Speci…cally, we employ a particular version of a wavelet transformation of a time series called the Maximal Overlap Discrete Wavelet Transform (MODWT). 5 As an example, by using the speci…c form of a Haar wavelet …lter, any time series X t can be decomposed into a scale component S J;t and J detail components D j;t :…”
Section: Methodology and Datamentioning
confidence: 99%
“…If J is small, then the scale component includes ‡uctuations of shorter duration, which one may not normally associate with a trend. 8 An alternative interpretation is that S J;t is the 5 The MODWT version of the wavelet …lter has become the standard in the empirical …nance and forecasting literature, e.g. Berger (2016) or Faria and Verona (2018).…”
Section: Methodology and Datamentioning
confidence: 99%
“…to measure the co-movements among financial time series, and nowadays there is a vast and growing literature on this topic (see for instance the following recent studies: Bartram & Wang, 2015;Berger, 2016;Durante et al, 2014Ling et al, 2015;Min & Czado, 2014;Shahzad et al, 2016;Wang & Xie, 2016;Weng & Gong, 2016). Copulas have also been used in studies related to applied economics, such as tourism (Pérez-Rodríguez et al, 2015;Tang et al, 1959;Zhu et al, 2016) and agriculture.…”
Section: Introductionmentioning
confidence: 99%